Level, Slope, Curvature: Characterising the Yield Curve in a Cointegrated VAR Model - Julia V. Giese (Kiel Institute for the World Economy (IfW), 2008)
Empirical evidence on the expectations hypothesis of the term structure is in-conclusive and its validity widely debated. Using a cointegrated VAR model of US treasury yields, this paper extends a common approach to test the theory. If, as we find, spreads between two yields are non-stationary, the expectations hypothesis fails. However, we present evidence that differences between two spreads are stationary. This suggests that the curvature of the yield curve may be a more meaningful indicator of expected future interest rates than the slope. Furthermore, we characterise level and slope by deriving the common trends inherent in the cointegrated VAR, and establish feedback patterns between them and the macroeconomy.
Keywords: E43; C32; E44; 330; Yield Curve; Term Structure of Interest Rates; Expectations Hypothesis; Cointegration; Common Trends; Zinsstruktur; VAR-Modell; Zinsstrukturtheorie; Theorie; USA